2018
DOI: 10.1002/ijgo.12702
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of the association between chromosomal polymorphisms and outcomes of embryo transfer following in vitro fertilization and/or intracytoplasmic sperm injection

Abstract: Background The outcomes of in vitro fertilization and/or intracytoplasmic sperm injection (IVF/ICSI) are contradictory among individuals with chromosomal polymorphisms. Objectives To assess whether chromosomal polymorphisms affect the outcomes of assisted reproductive technologies. Search strategy Four online databases were searched from inception to September 18, 2017, using terms including “chromosomal polymorphisms” and “In vitro fertilization.” Selection criteria The meta‐analysis included studies publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
2
6
1
Order By: Relevance
“…Then, the PGT data were analyzed for CTCPM carriers and CT carriers. Embryo development suggests that CPM is associated with multinucleated embryo formation (Sun et al, 2018) and has an impact on fertilization rate, embryo cleavage rate, high-quality embryo rate, and live birth rate (Liang et al, 2014;Ou et al, 2019). However, in our data, there was no statistical difference in fertilization rate, cleavage rate on Day 3, blastocysts rate, or highquality blastocyst rate between CPM carriers and patients with normal chromosomes.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…Then, the PGT data were analyzed for CTCPM carriers and CT carriers. Embryo development suggests that CPM is associated with multinucleated embryo formation (Sun et al, 2018) and has an impact on fertilization rate, embryo cleavage rate, high-quality embryo rate, and live birth rate (Liang et al, 2014;Ou et al, 2019). However, in our data, there was no statistical difference in fertilization rate, cleavage rate on Day 3, blastocysts rate, or highquality blastocyst rate between CPM carriers and patients with normal chromosomes.…”
Section: Discussioncontrasting
confidence: 75%
“…The high-quality blastocyst rate decreased, and the differences were mainly observed when one spouse had CTCPM, especially male patients, which was consistent with other studies. The study showed that variability in the retention of nucleosomes could interfere with constitutive heterochromatin function in the zygote and so affect the developmental potential of the embryo (Ou et al, 2019). These results may suggest that for CT, CPM may not affect embryo development, but it can decrease the high-quality blastocyst rate in ICSI-PGT.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although ARTs are considered safe, the in vitro environment differs significantly from that in vivo and involves multiple sources of stress for the embryo that can affect the epigenetic reprogramming that occurs during early embryo development (Ghosh, Coutifaris, Sapienza, & Mainigi, ). In humans, many other factors could also affect embryo quality, such as fertility problems or patient age (Ross, & Canovas, ) and male but not female chromosome polymorphisms (Ou et al, ). For ethical reasons, naturally conceived healthy embryos cannot be used as controls for studies in humans.…”
Section: Embryo Responses To Art‐induced Stress In Humansmentioning
confidence: 99%